Story as Pedagogy: A Reflective Commentary (LEARNing Landscapes, 2018)
This commentary seeks to encourage reflection upon learning and teaching through story. The authors illustrate ways they have used story in their teaching and what they perceive as the benefits of doing so. They explore how they learned through narrative as children and why they came to value it as a way of seeing and thinking. Then they consider how story disciplined their approaches to professional work before identifying specific narrative strategies used in teaching undergraduate and graduate students. The article concludes with suggestions about ways to better integrate narrative practices into teaching and learning.
Keywords: teaching and learning through story; narrative strategies; story as pedagogy